Market Power in the Nordic Wholesale Electricity Market: A Survey of the Empirical Evidence - Sven-Olof Fridolfsson; Thomas Tangerås (Research Institute of Industrial Economics (IFN), 2008)
We review the recent empirical research concerning market power on the Nordic wholesale market for electricity, Nord Pool. There is no evidence of blatant and systematic exploitation of system level market power on Nord Pool. However, generation companies seem from time to time able to take advantage of capacity constraints in transmission to wield regional market power. Market power can manifest itself in a number of ways which have so far escaped empirical scrutiny. We discuss investment incentives, vertical integration and buyer power, as well as withholding of base-load (nuclear) capacity.
Keywords: L13; L94; Q41; 330; Electricity Markets; Deregulation; Market Power; Hydro Power; Transmission Constraints; Elektrizitätswirtschaft; Marktmacht; Deregulierung; Wasserkraft; Elektrizitätsversorgung; Nordeuropa